SAFE BEHAVIOR OF CHILDREN WITH MENTAL DISORDERS AS AN OBJECT OF PSYCHOLOGICAL RESEARCH - Lidija Favarisovna Fatihova (Science and Innovation Center Publishing House, 2019)
Purpose. The article proposes a theoretical analysis of the problem of safe behavior of children and adolescents. The authors consider such concepts as «safe behavior», «safety culture», «concept of security», «life safety», «safe type personality».